Effect of Folic Acid Intake on Infant and Child Allergic Diseases: Systematic Review and Meta-Analysis - Chen, Zekun; Xing, Yan; Yu, Xue; Dou, Yuqi; Ma, Defu (Frontiers in Pediatrics, 2021)
Objective: This study aimed to comprehensively collect and summarize relevant data and analyze the effect of folic acid supplements on infant and child allergic diseases via systematic review and meta-analysis. Design: PubMed, The Cochrane Library and references of related articles published before January 1, 2020 were searched. Setting: Meta-analysis was used to explore the influence of folic acid on skin allergies (eczema, and atopic dermatitis) and respiratory allergies (asthma, wheezing, and allergic rhinitis). Participants: Data were collected from fifteen studies with 244,018 individual participants from five different countries for meta-analysis Results: Folic acid was confirmed as a risk factor for allergic diseases in infant and child. The risk of allergic diseases dramatically increased when maternal folic acid intake less than 400 µg/day (RR=1.050; 95% CI=1.027–1.073) during pregnancy. Stratified analyses revealed that the association was significant only for respiratory allergy (RR=1.067; 95% CI=1.028–1.108) and pregnant women who only used folic acid supplements (RR=1.070; 95% CI=1.030–1.112) and that countries without folic acid fortification (RR=1.046; 95% CI=1.026–1.067). that when pregnant women only used folic acid supplements (RR=1.070; 95% CI=1.025–1.117) and that countries without folic acid fortification (RR=1.046; 95% CI=1.026–1.067). Conclusions: This study suggested that inadequate folic acid intake can be a risk factor for allergic diseases, especially respiratory tract allergies among infants and young children. Furthermore, pregnant women should pay attention to supplementation of folic acid from both folic acid supplements and fortified foods with folic acid during pregnancy.